2021
DOI: 10.1021/acsami.0c19287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stabilities and Production Yields of MAPbBr3 Quantum Dots and Their Applications as Stretchable and Self-Healable Color Filters

Abstract: Organic–inorganic hybrid CH3NH3PbBr3 (MAPbBr3) perovskite quantum dots (PQDs) are considered as promising and cost-effective building blocks for various optoelectronic devices. However, during centrifugation for the purification of these PQDs, commonly used polar protic and aprotic non-solvents (e.g., methanol and acetone) can destroy the nanocrystal structure of MAPbBr3 perovskites, which will significantly reduce the production yields and degrade the optical properties of the PQDs. This study demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…2 . Before the quenching experiment, we noticed a blue shift in the emission peak of the PNC samples as compared to a previous report 47 due to the dilution effect.…”
Section: Methodssupporting
confidence: 46%
“…2 . Before the quenching experiment, we noticed a blue shift in the emission peak of the PNC samples as compared to a previous report 47 due to the dilution effect.…”
Section: Methodssupporting
confidence: 46%
“…Yang et al [119] compounded PQDs and thermoplastic elastomer into a stretchable and self-healing filter film. Furthermore, they fabricated and sequentially stacked green (MAPbBr 3 ) and red (CsPbBr 0.6 I 2.4 ) composite films, which can be excited by a blue LED to realize white light.…”
Section: Pqd Color Conversion Layermentioning
confidence: 99%
“…To investigate the effects of the water-assisted procedure on a perovskite crystal structure on the prepared MAPbBr 3 PeQDs, their XRD patterns were measured. From XRD patterns, the prepared samples with between 0 vol% and 0.16 vol% of assisting water obviously show the strong peaks attributed to the (100), ( 110), ( 200), ( 210), (220), and (300) diffraction planes (Figures 4 and S3), which indicated a cubic perovskite crystal structure [23,24]. The XRD patterns results showed that the optimal water-assisted content will not have a negative effect on the crystal structure.…”
Section: The Effect Of the Assisting Water On The Prepared Mapbbr 3 Peqdsmentioning
confidence: 99%